2022
DOI: 10.1177/10944281221127292
|View full text |Cite
|
Sign up to set email alerts
|

Review Research as Scientific Inquiry

Abstract: This article and the related Feature Topic at Organizational Research Methods upcoming were motivated by the concern that despite the bourgeoning number and diversity of review articles, there was a lack of guidance on how to produce rigorous and impactful literature reviews. In this article, we introduce review research as a class of research inquiries that uses prior research as data sources to develop knowledge contributions for academia, practice and policy. We first trace the evolution of review research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 201 publications
(390 reference statements)
0
37
0
Order By: Relevance
“…The volume of research published in academic journals and other outlets has significantly increased over the past few decades (Booth et al , 2021; Kraus et al , 2021), and business research, including accounting research, is no exception (Andiola et al , 2017; Dyckman and Zeff, 2015; Kraus et al , 2020; Kunisch et al , 2018, 2023; Paul and Criado, 2020; Snyder, 2019; Zeff, 2019). Hence, researchers, especially junior scholars such as PhD students, may find it difficult to stay up-to-date in their area of interest and recognize which relevant and interesting research questions remain to be answered (Petticrew and Roberts, 2012; Kraus et al , 2021).…”
Section: The Increasing Relevance Of Review-centric Work In and Beyon...mentioning
confidence: 99%
See 2 more Smart Citations
“…The volume of research published in academic journals and other outlets has significantly increased over the past few decades (Booth et al , 2021; Kraus et al , 2021), and business research, including accounting research, is no exception (Andiola et al , 2017; Dyckman and Zeff, 2015; Kraus et al , 2020; Kunisch et al , 2018, 2023; Paul and Criado, 2020; Snyder, 2019; Zeff, 2019). Hence, researchers, especially junior scholars such as PhD students, may find it difficult to stay up-to-date in their area of interest and recognize which relevant and interesting research questions remain to be answered (Petticrew and Roberts, 2012; Kraus et al , 2021).…”
Section: The Increasing Relevance Of Review-centric Work In and Beyon...mentioning
confidence: 99%
“…Because such evidence-based reviews focus on a phenomenon observed in organizational practice or a related question, they would mostly apply to use case (i) reviews of a certain domain of accounting research. Authors of evidence-based reviews usually collect all relevant research items that can shed light on the phenomenon (Kunisch et al , 2023; Rousseau et al , 2008) – without defining in advance on which theoretical basis the research items must rest to qualify for inclusion in the review sample. Researchers may then inductively – and thus, without a predefined theoretical framework in mind – analyze the review sample.…”
Section: Challenges Potential Solutions and Opportunities For Reviews...mentioning
confidence: 99%
See 1 more Smart Citation
“…Management scholars have increasingly recognized the distinct nature and value of review articles to make knowledge contributions (e.g., Kunisch et al., 2023; McMahan & McFarland, 2021; Rojon et al., 2021; Siddaway et al., 2019; Snyder, 2019). In general, this form of scholarly inquiry ‘employs scientific methods to analyse and synthesize prior research to develop new knowledge for academia, practice and policy‐making’ (Kunisch et al., 2023: 5).…”
Section: Review Articles and Societal Grand Challengesmentioning
confidence: 99%
“…Management scholars have increasingly recognized the distinct nature and value of review articles to make knowledge contributions (e.g., Kunisch et al., 2023; McMahan & McFarland, 2021; Rojon et al., 2021; Siddaway et al., 2019; Snyder, 2019). In general, this form of scholarly inquiry ‘employs scientific methods to analyse and synthesize prior research to develop new knowledge for academia, practice and policy‐making’ (Kunisch et al., 2023: 5). Review articles can build an actionable knowledge base because they identify accumulated research on the same problem, thus overcoming the limitations of a single study (Denyer & Tranfield, 2006).…”
Section: Review Articles and Societal Grand Challengesmentioning
confidence: 99%